Reason and analysis in ancient Greek Philosophy : essays in honor of David Keyt - Miller Jr., Fred D.; Anagnostopoulos, Georgios (Philosophical Studies Series, 2013)
This distinctive collection of original articles features contributions from many of the leading scholars of ancient Greek philosophy.  They explore the concept of reason and the method of analysis and the central role they play in the philosophies of Socrates, Plato, and Aristotle.   They engage with salient themes in metaphysics, epistemology, ethics, and political theory, as well as tracing links between each thinker's ideas on selected topics. The volume contains analyses of Plato's Socrates, focusing on his views of moral psychology, the obligation to obey the law, the foundations of politics, justice and retribution, and Socratic virtue. On Plato's Republic, the discussions cover the relationship between politics and philosophy, the primacy of reason over the soul's non-rational capacities, the analogy of the city and the soul, and our responsibility for choosing how we live our own lives. The anthology also probes Plato's analysis of logos (reason or language) which underlies his philosophy including the theory of forms. A quartet of reflections explores Aristotelian themes including the connections between knowledge and belief, the nature of essence and function, and his theories of virtue and grace.  The volume begins with an intellectual memoir by David Keyt that recounts his adventures as a philosopher and scholar during the rise of analytic classical scholarship in the past century. Along the way, Keyt relates entertaining anecdotes involving major figures in modern academic philosophy. Blending academic authority with creative flair and demonstrating the continuing interest of ancient Greek philosophy, this book will be a valuable addition to the libraries of all those studying and researching the origins of Western philosophy.